Pemantauan Berkala Elevasi Dan Kemiringan Konstruksi Gedung Sebelum Penerbitan Sertifikat Laik Fungsi: A Preliminary Study - Masykur Kimsan (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
Periodic monitoring of elevation and tilt is essential in ensuring the safety and functionality of buildings over time. This practice, mandated by regulations such as PP 16/2021, helps identify potential structural issues before the issuance of occupancy certificates. Beyond safety, monitoring also considers occupants' comfort and overall building performance. Understanding elevation and tilt is crucial, as these can indicate structural problems. Monitoring must be meticulous, using suitable methods and accounting for environmental factors like temperature and wind. Implementing periodic monitoring faces challenges, including selecting appropriate methods and managing costs and resources. In Indonesia, where buildings are often old and environmental conditions extreme, monitoring is especially vital. Historical buildings require unique monitoring to preserve their architectural heritage. This study aims to enhance understanding of periodic monitoring's importance and effective methods, benefiting practitioners and researchers. It emphasizes monitoring's role in ensuring building safety, quality, and sustainability, underscoring the need for ongoing research in this area.